Reinvestigating the export-led growth evidence in Malaysia: bound test approach / Maymunah Ismail, Maizatul Saadiah Mohammad and Abdul Rahim Ridzuan - Ismail, Maymunah; Mohammad, Maizatul Saadiah; Ridzuan, Abdul Rahim (2013)
This paper re-investigates the evidence of Export-Led-Growth Hypothesis by using recent time series techniques known as Bound test or also known as ARDL approach. The data used in this paper is annually data range from 1980 to 2011. By modifying the standard Cobb Douglas production function, we found out that export play significant role in contributing growth to the Malaysia's economy besides, labour and capital are also importance for the development of the nation. We recommend few policies based on the result gain from this paper.